2016
DOI: 10.1080/2162402x.2015.1116674
|View full text |Cite
|
Sign up to set email alerts
|

The proto-oncogene Myc drives expression of the NK cell-activating NKp30 ligand B7-H6 in tumor cells

Abstract: Natural Killer (NK) cells are innate effector cells that are able to recognize and eliminate tumor cells through engagement of their surface receptors. NKp30 is a potent activating NK cell receptor that elicits efficient NK cell-mediated target cell killing. Recently, B7-H6 was identified as tumor cell surface expressed ligand for NKp30. Enhanced B7-H6 mRNA levels are frequently detected in tumor compared to healthy tissues. To gain insight in the regulation of expression of B7-H6 in tumors, we investigated tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 44 publications
(57 reference statements)
0
36
1
Order By: Relevance
“…Furthermore, treatment of tumor cells with almost all standard tumor therapeutics, including chemotherapy, radiation therapy, non-lethal heat shock, and cytokine therapy (TNFα) can upregulate the expression of B7-H6 in tumor cells and enhance tumor sensitivity to NK cell cytolysis (90). Pharmacological inhibition or siRNA/shRNA-mediated knock-down of c-Myc or N-Myc significantly decreases B7-H6 expression on a variety of tumor cells including melanoma, pancreatic carcinoma and neuroblastoma cell lines (91). In tumor cell lines from different origin and primary tumor tissues of HCC, lymphoma and neuroblastoma, mRNA levels of c-Myc positively correlate with B7-H6 expression.…”
Section: B7-h6mentioning
confidence: 99%
“…Furthermore, treatment of tumor cells with almost all standard tumor therapeutics, including chemotherapy, radiation therapy, non-lethal heat shock, and cytokine therapy (TNFα) can upregulate the expression of B7-H6 in tumor cells and enhance tumor sensitivity to NK cell cytolysis (90). Pharmacological inhibition or siRNA/shRNA-mediated knock-down of c-Myc or N-Myc significantly decreases B7-H6 expression on a variety of tumor cells including melanoma, pancreatic carcinoma and neuroblastoma cell lines (91). In tumor cell lines from different origin and primary tumor tissues of HCC, lymphoma and neuroblastoma, mRNA levels of c-Myc positively correlate with B7-H6 expression.…”
Section: B7-h6mentioning
confidence: 99%
“…B7-H6 is not normally expressed on healthy cells, but can be upregulated on human tumor cells through a Myc-mediated mechanism (86) or upon stimulation of monocytes and neutrophils with TLR ligands or pro-inflammatory cytokines (87). Upon recognition by NKp30, B7-H6 triggers cytotoxicity and cytokine production by NK cells (52).…”
Section: Ligands Of the Ncrsmentioning
confidence: 99%
“…20 They also showed that melanoma cell exposure to histone deacetylase inhibitors, known for their ability to increase the expression of ligands for NK activator receptors, 40 restored NK-mediated killing. Thus, B7H6 promoter analysis revealed functional binding sites for Sp1 and Myc, 41 while ULBP2 and ULBP3 expression in AML is dependent on c-Myc. 21 Indeed, they showed an upregulatory trend of B7H6 expression paralleled by a reduction of ULBP2 expression and HLA class I molecules, resulting overall in a reduced NK cell-mediated killing.…”
Section: Discussionmentioning
confidence: 93%
“…The surface expression of both B7H6 and ULBP3 has been related to oncogenic-driven molecular pathways. Thus, B7H6 promoter analysis revealed functional binding sites for Sp1 and Myc, 41 while ULBP2 and ULBP3 expression in AML is dependent on c-Myc. 42 Furthermore, the upregulation of specific kinase pathways can drive the expression of NK ligands, and the activation of AKT-PI3K and RAS-RAF has been proved to play a role in the upregulation of NKG2D ligands.…”
Section: Discussionmentioning
confidence: 93%